"Mednarodno življenje" arbitražne odločbe o meji med Slovenijo in Hrvaško - Sancin, Vasilka (Podjetje in delo, 2024)
On 4 November 2009, the Prime Ministers of Croatia and Slovenia signed an Arbitration Agreement, by which Croatia and Slovenia decided to submit their border dispute to arbitration; just under eight years later, on 29 June 2017, the Arbitral Tribunal rendered its Final Award at a public sitting at the Peace Palace in The Hague. Beforehand, the Arbitral Tribunal in its Partial Award on 30 June 2016 found that albeit Slovenia has violated provisions of the Arbitration Agreement, it remains in force and necessitates continuation of arbitral proceedings. Croatia decided not to participate in the remaining proceedings and also entirely rejected the arbitral award. The award is being implemented only by Slovenia, which continuously calls on Croatia to respect its international legal commitments. Slovenia sought to prove before the Court of Justice of the European Union, and its citizens before the European Court of Human Rights, with Slovenia's intervention, violations of obligations by Croatia under EU law and the European Convention on Human Rights, respectively. While in the first case, the court declared itself without jurisdiction, in the second instance, the section of the court declared the complaints inadmissible. Nevertheless, these decisions of the two courts raised some pertinent questions that deserve further attention also by international law scholars, which is highlighted in this article. It remains to be seen when and under what conditions will the situation on the ground be settled in accordance with the final and binding award or, potentially, any settlement included in a subsequently concluded agreement, should the two states decide to follow this path. Some ideas on how to further a meaningful 'international life' of the arbitral award are included in this article.
Keywords: Mednarodna arbitraža; Mednarodno pravo